An assessment of threats to terrestrial protected areas - Schulze, K.; Knights, K.; Geldmann, J.; Leverington, F.; Eassom, A.; Marr, M.; Butchart, S.H.M.; Hockings, M.; Burgess, Neil D.; Coad, L.M. (Wiley, 2018)
Protected areas (PAs) represent a cornerstone of efforts to safeguard biodiversity, and if effective should reduce threats to biodiversity. We present the most comprehensive assessment of threats to terrestrial PAs, based on in situ data from 1,961 PAs across 149 countries, assessed by PA managers and local stakeholders. Unsustainable hunting was the most commonly reported threat and occurred in 61% of all PAs, followed by disturbance from recreational activities occurring in 55%, and natural system modifications from fire or its suppression in 49%. The number of reported threats was lower in PAs with greater remoteness, higher control of corruption, and lower human development scores. The main reported threats in developing countries were linked to overexploitation for resource extraction, while negative impacts from recreational activities dominated in developed countries. Our results show that many of the most serious threats to PAs are difficult to monitor with remote sensing, and highlight the importance of in situ threat data to inform the implementation of more effective biodiversity conservation in the global protected area estate.